Pengaruh Fraud Triangle terhadap Kecurangan Laporan Keuangan - Salsabila Alya Maharany; Sofinatus Solikhah; Arfenita Cahyaningrum; Tries Ellia Sandari (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study aims to analyze how the elements of the Fraud Triangle, namely pressure, opportunity, and rationalization, influence the occurrence of financial statement fraud. Using a qualitative method with a descriptive approach and secondary data sources from relevant literature published in 2020–2025, this study examines various previous research findings related to the application of the Fraud Triangle theory in the industrial sector in Indonesia and internationally. The study results indicate that pressure, especially in the form of high financial targets and external pressure, is the dominant factor that triggers management to manipulate reports. Meanwhile, opportunity does not always have a significant impact on fraud due to the presence of effective internal control systems and external supervision. Rationalization has been proven to also drive fraudulent actions through moral justification by the perpetrators. This study concludes that the Fraud Triangle remains a relevant conceptual framework in understanding and detecting potential financial statement fraud, as well as providing implications for improving corporate governance and control systems.